Reflectivity towards improving postgraduate student research supervision: A digital lens on the University of Namibia - Haipinge, E.; Kadhila, N.; Josua, L. M. (South African Journal of Higher Education, 2025)
The purpose of this paper is to explore student supervision in research at the University of Namibia and propose interventions that enhance effective postgraduate student research supervision using digital technology. The paper employed Barry Stierer’s methods of critical reflection dictated by the three domains namely, criticality, reflexivity, and praxis. These methods are further used to support critical reflection of the context and make interpretations related to the use of technology to enhance student supervision in higher education institutions in general and at the University of Namibia in particular. This paper revealed that student supervision in research is not taken as a mean to enable pedagogic access. There is no institutional common procedures or model of postgraduate student research supervision leading to academics adopting the supervisory methods they have experienced when they were supervised. The paper contributed to theory, practice and policy that research supervision is taken as a common sense than a scientific approach. However, it recommended that postgraduate student research supervision can benefit from digital technology just like teaching and learning as well as assessment.